Isolation and recrystallization of epicuticular waxes from Sorbus and Cotoneaster leaves - Ganeva Tsveta; Stefanova Miroslava; Koleva Dimitrina; Ruiz Segundo Ríos (Open Life Sciences, 2015)
Wax morphology and chemical composition are widely accepted to be important for the protective properties of the leaf’s surface and also valuable characteristics in plant systematics. The leaves of Sorbus domestica L. and Cotoneaster granatensis Boiss., species of two large genera with intricate taxonomy referred to subtribe Pyrinae, Rosaceae (formerly subfamily Maloideae), were studied by scanning electron microscope (SEM) and performing different methods of wax isolation. The aim of the study was to acquire a suitable, cost and time effective method for wax removal. Chloroform and methanol extractions and freeze-embedding method for direct isolation of the wax crystals were applied. Immersing the leaves for 3 minutes in chloroform was sufficient to extract the waxes whereas the efficiency of the methanol solvent was lower. Wax layers with wellpreserved structures of the crystals from both upper and lower epidermis were successfully transferred to artificial surfaces. The recrystallization experiment demonstrated that waxes from chloroform extracts could recrystallize in in vitro conditions on artificial surfaces. The crystals showed same micromorphology as on the intact leaves. Results of this study could be applied in further analytical researches of the waxes of S. domestica and C. granatensis or other species of the subtribe Pyrinae.